Physical activity as a causal variable for adolescent resilience levels: A cross-lagged analysis - Guo, Lingling; Liang, Lulu (Frontiers in Psychology, 2023)
This study extends research on the relationship between physical activity and adolescent resilience by using cross-lagged analysis. Therefore, it used the Adolescent Resilience Rating Scale and the Physical Activity Scale to conduct a one-year longitudinal follow-up survey on 818 adolescents (50.6% boys), aged 12–17. They completed the questionnaires, providing data on physical activity and adolescent resilience. The results indicated there were significant gender differences in physical activity, but there was no significant gender difference in adolescent resilience; there was a significant positive correlation between physical activity and adolescent resilience; physical activity had a significant predictive effect on adolescent resilience. This study supports the assertion that physical activity has an important impact on adolescent resilience. It further analyzes the possible reasons for this result and contemplates the theoretical and practical significance of the findings, which provides evidence for the study of adolescents’ physical and mental health and enriches the theory of resilience.